The Relationship Between Self-Confidence and Public Speaking Anxiety Among University Students - Salsabilla Tarigan; Doli Maulana Gama Samudera Lubis (Psikologi Prima, 2026)
This study aimed to examine the relationship between self-confidence and public speaking anxiety among students of the Faculty of Law at Universitas Medan Area. The study employed a quantitative approach with a correlational research design. The research population consisted of 354 active students, with a sample of 102 students selected using a purposive sampling technique. The research instruments consisted of a 24-item self-confidence scale and a 20-item public speaking anxiety scale, both using a five-point Likert scale model. The instruments underwent adaptation procedures, content validity assessment, and reliability testing, resulting in Cronbach’s Alpha coefficients of 0.87 for the self-confidence scale and 0.89 for the public speaking anxiety scale. Data analysis was conducted using IBM SPSS through descriptive statistics, normality testing, linearity testing, and Pearson Product Moment correlation analysis. The findings revealed a significant negative relationship between self-confidence and public speaking anxiety, with a correlation coefficient of r = -0.71 and p = 0.000 (p < 0.05). The coefficient of determination of 0.51 indicated that self-confidence contributed 51% to the variance in public speaking anxiety. These findings suggest that students with higher levels of self-confidence tend to experience lower levels of public speaking anxiety. However, because this study employed a correlational design, the findings cannot be interpreted as evidence of a causal relationship.